Popular heritage: concept and sections - Nouadrya, Karima; Zadam, Souad (Milev Journal of Research and Studies, 2017)
In this paper, theoretical concepts were introduced that could introduce a study of the effect of the heritage - especially popular - on the general life of man, as this kind of heritage is one of the creative genres that Dig deep into the human entity so that it becomes an integral part of it. Even a solid support preserving its cultural and civilizational identity in the midst of current challenges and changes.